จลนพลศาสตร์และผลของแอมโมเนียต่อจำนวนยีน amoA ของแอมโมเนียออกซิไดซ์ซิงอาร์เคียและ แอมโมเนียออกซิไดซ์ซิงแบคทีเรีย - ภัทรพร คุนาพงษ์กิติ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The objectives of this study are to investigate the effect of ammonia on abundance of amoA genes of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) and the kinetics of ammonia oxidation in mixed nitrifying cultures that contained different groups of ammonia oxidizers. Enrichment of mixed nitrifying cultures was performed with two sets of experiments. Each set of experiment comprised of five batch reactors receiving influent with different ammonium concentrations (14 28 70 280 and 420 mg N l⁻¹). The first set of experiment used seed sludge from Nhong Kham wastewater treatment plant that contained only amoA genes of AOB, while the second set of experiment used seed sludge from Din Dang wastewater treatment plant that contained amoA genes of both AOA and AOB. During enrichment, sludge samples were taken from each reactor and analysed for abundance of amoA genes of AOA, AOB and Nitrosomonas oligotropha and 16S rRNA of Nitrosomonas europaea using qPCR technique. After steady state of operation, the KS values of the sludge were determined. The results showed that ammonium concentrations in the reactors affect the abundance of amoA genes of AOA, AOB and Nitrosomonas oligotropha and 16S rRNA of Nitrosomonas europaea. In the reactor with low ammonium levels amoA genes of AOA were found together with amoA genes of AOB (average ammonium concentrations at the end of cycle were 0-2.1 mg N l⁻¹), but in the reactors with high ammonia levels only amoA genes of AOB were found (average ammonium concentrations at the end of cycle were 10-150 mg N l⁻¹). In the reactors with low ammonium levels, only Nitrosomonas oligotropha were found, while in the reactors with high ammonium levels, Nitrosomonas europaea were found in high numbers. The results suggested that the occurrence of ammonia oxidizers in the reactors related to the KS values of ammonia-oxidizing species and the ammonium levels in the reactors. The KS values of mixed nitrifying cultures taken from different reactors varied depending on the AOB species found in the reactors. In the reactors with low ammonium levels where the KS values of mixed nitrifying cultures was in the range of 0.6-3.3 mg N l⁻¹ and the KS values from the reactors with high ammonium levels was 10.1-24.6 mg N l⁻¹. Although in some reactors with low ammonium levels both AOA and AOB (Nitrosomonas oligotropha) occurred, the KS values fell in the range of Nitrosomonas oligotropha, not AOA.